Future Policy Award 2018: The Good Food Purchasing Program, USA - Daniels, Paula; Delwiche, Alexa (Frontiers in Sustainable Food Systems, 2022)
Adopted first by the City of Los Angeles in 2012, the Good Food Purchasing Program ® creates a transparent supply chain and helps institutions to measure and then make shifts in their food purchases. It is the first procurement model to support five food system values – local economies, environmental sustainability, valued workforce, animal welfare and nutrition – in equal measure and thereby encourages myriad organizations to come together to engage for shared goals. Within just six years, the Good Food Purchasing Program has catalyzed a nationwide movement to establish similar policies in localities small and large across the United States, and inspired the creation of the Center for Good Food Purchasing. First adopted by the City of Los Angeles in 2012, it is a procurement standard that offers institutions a system in which current investments towards food are redirected towards more sustainable and fair suppliers. It uses a metric-based, flexible framework that produces a star rating. The Good Food Purchasing Program promotes the purchase of more sustainably produced food, from local economies, especially smaller and mid-sized farms and other food processing operations, which results in production returns at a more regional and local level, and ensures that suppliers’ workers are offered safe and healthy working conditions and fair compensation, that livestock receives healthy and humane care, and that consumers – foremost school children, patients, the elderly – enjoy better health and well-being as a result of higher quality nutritious meals. This article will detail its implementation since 2012, provide current information on the impacts the Program has had on the agroecology of regions in the US food system, and recommendations for policy changes that could catalyze more accelerated impact.